Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

if $\phi(x)={1\over x}\int_0^x F(t)dt$ and $F(x):=\int_0^x f(t)dt$ ,how does $$\phi'(x)=-{1\over x^2}\int_0^xF(t)dt +{1\over x}F(x)={1\over x^2}\int_0^x t f(t)dt\ ?$$

Please explain step by step since I am confused how to get to the last two equalities.

share|improve this question
2  
Out of curiosity, what have you tried so far? It is easier to help and give advice if you tell us exactly where you are stuck. –  Eric Naslund Jul 20 '11 at 17:55
    
@Dylan Moreland - i am not that advanced... –  Victor Jul 20 '11 at 18:43
    
@Dylan: I am curious, how does the above feature in the proof of Hardy's inequality? –  Eric Naslund Jul 20 '11 at 18:53
add comment

2 Answers

up vote 4 down vote accepted

Here are two hints. Give it a try, I can expand on the details for Hint 2 if needed.

Hint 1: $$\phi^'(x)=\frac{d}{dx} \frac{1}{x}\int_0^x F(t)dt=\left(\frac{d}{dx}\frac{1}{x}\right)\int_0^xF(t)dt+\frac{1}{x}\left(\frac{d}{dx}\int_0^x F(t)dt\right).$$ Then the fundamental theorem of calculus says $$\left(\frac{d}{dx}\int_0^x F(t)dt\right)=F(x).$$ Also, $$\frac{d}{dx}\frac{1}{x}=\frac{-1}{x^2}.$$

Hint 2: For any nice function $f$, we have that $$\int_0^x \int_0^t f(u) du dt= \int_0^x (x-t)f(t)dt.$$ This is a case of Cauchy's formula for repeated integration.

Hope that helps,

share|improve this answer
    
very concise,thanks! –  Victor Jul 20 '11 at 18:33
add comment

For our purposes, we may assume that $f$ is continuous.

Step 1: $$ \phi '(x) = \bigg(\frac{d}{{\,dx}}\frac{1}{x}\bigg)\int_0^x {F(t)\,dt} + \frac{1}{x}\frac{d}{{\,dx}}\int_0^x {F(t)\,dt}. $$

Step 2: $$ \phi '(x) = - \frac{1}{{x^2 }}\int_0^x {F(t)\,dt} + \frac{1}{x}F(x). $$

Step 3: $$ x^2 \phi '(x) = - \int_0^x {F(t)dt} + xF(x) = xF(x) - \int_0^x {F(t)dt}. $$

Step 4 -- integration by parts: $$ \int_0^x {tf(t) \,dt} = tF(t) \big|_0^x - \int_0^x {\bigg(\frac{d}{{\,dt}}t \bigg)F(t)\,dt} = xF(x) - 0F(0) - \int_0^x {1F(t)\,dt} = xF(x) - \int_0^x {F(t)\,dt}. $$

Step 5: It follows that $$ x^2 \phi '(x) = \int_0^x {tf(t) \,dt}. $$

Step 6: It follows that $$ \phi '(x) = \frac{1}{{x^2 }}\int_0^x {tf(t) \,dt}. $$

EDIT: For the integration by parts (beginning of Step 4), note that $F$ is an antiderivative of $f$, since, by the Fundamental theorem of calculus, $$ F'(x) = \frac{d}{{dx}}F(x) = \frac{d}{{dx}}\int_0^x {f(t)dt} = f(x). $$ (Here we used the assumption that $f$ is continuous.)

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.